Comparison of emotional intelligence disorders and personality disorders - Mykhailova Валерія (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report to the III Scientific and Practical Conference with International Participation "Psychiatry, Narcology, Clinical Psychology and General Medical Practice: Interdisciplinary Issues of the Present", March 22-23, 2024, Kyiv - online.